2023
DOI: 10.1002/adhm.202301809
|View full text |Cite
|
Sign up to set email alerts
|

Complexation‐Induced Resolution Enhancement Pleiotropic Small Diameter Vascular Constructs with Superior Antibacterial and Angiogenesis Properties

Abstract: Abstract3D printing has been widely applied for preparing artificial blood vessels, which will bring innovation to cardiovascular disorder intervention. However, the printing resolution and anti‐infection properties of small‐diameter vessels (Φ < 6 mm) have been challenging in 3D printing. The primary objective of this research is to design a noval coaxial 3D printing post‐processing method for preparing small‐size blood vessels with improved antibacterial and angiogenesis properties. The coaxial printing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…Figure 2a displays the tensile stress−strain curves of the five groups of PCO hydrogels, and we can see that the tensile property is significantly influenced by the raw material ratio. As shown in Figure 2b, PCO-2 obtained the highest tensile strength of 0.75 ± 0.04 MPa and a tensile elastic modulus of 0.76 ± 0.02 MPa, being 1.4 times that of pure PVA hydrogel, far exceeding the PVA/alginate/charged chitosan artificial blood vessels 19 and bacterial nanocellulose/chitosan/heparin artificial blood vessels 35 reported to date. The loading− unloading cycling tests for 200 cycles with 20% strain at a constant tensile rate of 100 mm min −1 in Figures 2c, S4, and S5 further demonstrated that PCO-2 hydrogels have ideal elastic recovery, indicating their high tensile mechanical stability and fatigue resistance.…”
Section: Mechanical Properties Of Hydrogelsmentioning
confidence: 84%
See 3 more Smart Citations
“…Figure 2a displays the tensile stress−strain curves of the five groups of PCO hydrogels, and we can see that the tensile property is significantly influenced by the raw material ratio. As shown in Figure 2b, PCO-2 obtained the highest tensile strength of 0.75 ± 0.04 MPa and a tensile elastic modulus of 0.76 ± 0.02 MPa, being 1.4 times that of pure PVA hydrogel, far exceeding the PVA/alginate/charged chitosan artificial blood vessels 19 and bacterial nanocellulose/chitosan/heparin artificial blood vessels 35 reported to date. The loading− unloading cycling tests for 200 cycles with 20% strain at a constant tensile rate of 100 mm min −1 in Figures 2c, S4, and S5 further demonstrated that PCO-2 hydrogels have ideal elastic recovery, indicating their high tensile mechanical stability and fatigue resistance.…”
Section: Mechanical Properties Of Hydrogelsmentioning
confidence: 84%
“…Xu et al used a bioink mixture of alginate (Alg) and poly(vinyl alcohol) (PVA) for coaxial printing, and then the tube's outer surface was chemically modified with positively charged chitosan (CTS) through electrostatic interactions. 19 The modified PVA artificial blood vessel improved the biocompatibility, and no blockage occurred after 5 days of blood circulation in vitro. Anderson et al grafted the collagen-mimetic peptide onto PVA hydrogel surfaces by CDI chemistry.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Therefore, the development of novel biodegradable vascular grafts that provide suitable space, allowing cell proliferation, attachment, growth, migration on the scaffold, and subsequent formation of new blood vessels has become a research hotspot. , ,, However, novel vascular grafts still face several challenges, including postoperative infection, ,, excessive inflammatory response, , long-term patency, , and lack of nondestructive monitorability. , Significant advancements have been made in the development of a variety of scaffolds with distinct structures and compositions tailored to address the specific challenges mentioned above. For instance, Xu et al fabricated a decellularized CuSO 4 –Alg-PVA-CTS tubular vascular tissue engineering scaffold using coaxial 3D printing and post-treatment, which demonstrated synergistic antibacterial effects due to the release of Cu 2+ ions and the presence of CTS. Furthermore, the Cu 2+ ions were found to enhance EC proliferation and angiogenesis.…”
Section: Introductionmentioning
confidence: 99%